EXTERNAL AUDITOR APPOINTMENT IN INDONESIAN STATE-OWNED ENTERPRISES: THE ROLE OF POLITICAL CONNECTION AND ACCOUNTING IRREGULARITIES - Annastasia Joceline; Gatot Soepriyanto (Bina Nusantara University, 2023)
This research investigates how political connections and accounting irregularities affect the auditor appointment decision in Indonesian state-owned enterprises. This research considers auditor choice and switching decisions as its dependent variables. Political connection is calculated as a percentage of the firm's board of directors and commissioners with political connections. Accounting irregularities are calculated with Beneish M-Score. Employing the 235 firm-year observations from 2014 to 2018 using logit regression, this research documents the following results: (1) Political connection has a significant negative influence on auditor choice. (2) Accounting irregularities have a weak significant negative influence on auditor choice. (3) Political connection has no significant influence on auditor switching. (4) Accounting irregularities have no significant influence on auditor switching.